2017
DOI: 10.1111/1462-2920.13889
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Mg2+ contributes to the resistance of Pseudomonas aeruginosa to complement‐mediated opsonophagocytosis

Abstract: Pseudomonas aeruginosa adaptation to survive in the host hinges on its ability to probe the environment and respond appropriately. Rapid adaptation is often mediated by two-component regulatory systems, such as the PhoP/PhoQ system that responds to Mg ion concentration. However, there is limited information about the role of PhoQ in P. aeruginosa bloodstream infections. We used a murine model of systemic infection to test the virulence of a PhoQ-deficient mutant. Mutation of PhoQ impaired the virulence and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…A previous study revealed that mutation of phoQ attenuates the bacterial virulence in a murine bacteremia infection model which is due to the upregulation of oprH that serves as a binding target of the complement component C3 [59]. In addition, mutation of phoQ reduces the bacterial twitching motility, biofilm formation, cytotoxicity as well as virulence in a lettuce leaf and a chronic rat lung infection model [34].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that mutation of phoQ attenuates the bacterial virulence in a murine bacteremia infection model which is due to the upregulation of oprH that serves as a binding target of the complement component C3 [59]. In addition, mutation of phoQ reduces the bacterial twitching motility, biofilm formation, cytotoxicity as well as virulence in a lettuce leaf and a chronic rat lung infection model [34].…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of previously identified bacterial factors could interfere with the complement system in the HWB model. Thus, bacteria could alter C3b binding [19,36,55,[57][58][59][60], recruit negative complement regulators [18,20,61,62], break down complement proteins [15,63,64], or stabilize outer membrane integrity [65,66]. Consequently, bacterial resistance to complement activity appears to be multifactorial and strain-dependent, and should thus be investigated in a more systematic and uniform way to obtain a better overall picture of the complex interactions involved.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Previously, it was reported that oprH is highly induced when P. aeruginosa interacts with epithelia cells ( 33 ). Recent studies demonstrated that OprH is a binding target of mammalian surfactant protein A ( 34 ) and C3 complement ( 35 ), indicating accessibility by host factors. In addition, high levels of antibodies against OprH were identified in young children with cystic fibrosis ( 36 ), indicating its high immunogenicity.…”
Section: Resultsmentioning
confidence: 99%